Analysis and Design of Web-Based MSME Cashier Application Using the Waterfall Model - Putra, Muhammad irlansyah; Silalahi, Kevin Ronitua; Sinabutar, Paskaria; Harmaja, Okta Jaya (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2024)
The rapid advancement of information technology in Indonesia has provided numerous benefits such as increased work efficiency, expanded access to information, and enhanced connectivity. Additionally, technology has opened up new opportunities for business and job creation. However, on the other hand, there are several challenges that need to be addressed, such as digital divide, cybercrime, and social impacts that require management. Manual transaction systems have several drawbacks, particularly during high order volumes, resulting in inefficient recording and difficulty in tracking top-selling products. This is due to the limitations of manual sales transaction recording. Therefore, the use of a cashier application is necessary to streamline all transaction processes, including sales, payments, purchases, payroll, and inventory management. Point of Sale (POS) is a software and hardware solution specifically designed to facilitate these transactions. Despite the availability of many POS applications in the current market, they often do not meet the specific needs of SMEs and are relatively expensive, leading many SME operators to hesitate in adopting them. Based on observations and interviews with SME operators, there is a need for POS applications that not only cater to the specific requirements of SMEs but are also financially feasible.